2005
DOI: 10.1007/s10152-005-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical distribution of meiofauna on sandy beaches of the North Sea (The Netherlands, Belgium, France)

Abstract: Horizontal and vertical distribution of meiofauna on sandy beaches of the North Sea (The Netherlands, Belgium, France) Abstract Sandy intertidal zones were analysed for the presence of meiofauna. The material was collected on six macro-tidal sandy beaches along the North Sea (The Netherlands, France, Belgium), in order to analyse the vertical and horizontal meiofaunal distribution patterns. Eleven higher meiofauna taxa (one represented by larval stage-Copepoda nauplii) were recorded. The maximum total meiofaun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
4
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 43 publications
9
35
4
4
Order By: Relevance
“…In this study, the highest meiofauna densities were observed in the 10 to 30 cm strata. This contrasts with previous reports, according to which the highest meiofauna densities were generally observed in the top 10 cm of sediment (MCLACHLAN, 1978;OLAFSSON;ELMGREN, 1997;DE JESUS-NAVARRETE;HERRERA-GOMEZ, 2002;KAPUSTA et al, 2002;KOTWICKI et al, 2005). High densities at the sediment surface are generally related to the existence of an anoxic layer (chemical gradient) that forms immediately below the top centimeters of sediment in dissipative beaches (KOTWICKI et al, 2005), ultradissipative beaches (MARIA et al, 2012) and tidal flats (VIEIRA;FONSECA, 2013).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In this study, the highest meiofauna densities were observed in the 10 to 30 cm strata. This contrasts with previous reports, according to which the highest meiofauna densities were generally observed in the top 10 cm of sediment (MCLACHLAN, 1978;OLAFSSON;ELMGREN, 1997;DE JESUS-NAVARRETE;HERRERA-GOMEZ, 2002;KAPUSTA et al, 2002;KOTWICKI et al, 2005). High densities at the sediment surface are generally related to the existence of an anoxic layer (chemical gradient) that forms immediately below the top centimeters of sediment in dissipative beaches (KOTWICKI et al, 2005), ultradissipative beaches (MARIA et al, 2012) and tidal flats (VIEIRA;FONSECA, 2013).…”
Section: Discussioncontrasting
confidence: 82%
“…This contrasts with previous reports, according to which the highest meiofauna densities were generally observed in the top 10 cm of sediment (MCLACHLAN, 1978;OLAFSSON;ELMGREN, 1997;DE JESUS-NAVARRETE;HERRERA-GOMEZ, 2002;KAPUSTA et al, 2002;KOTWICKI et al, 2005). High densities at the sediment surface are generally related to the existence of an anoxic layer (chemical gradient) that forms immediately below the top centimeters of sediment in dissipative beaches (KOTWICKI et al, 2005), ultradissipative beaches (MARIA et al, 2012) and tidal flats (VIEIRA;FONSECA, 2013). However, on reflective beaches, such as Estaleiro and Estaleirinho Beaches, the low densities in the 0-10 cm stratum resulted from the re-suspension of the top centimeters of sediment by the wave energy (MCLACHLAN, 1989;BROWN, 2006), which conditioned the meiofauna to live in intermediate strata.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The lower compartment was inserted 10 cm deep into the sediment. This depth was chosen since vertical penetration of copepods happens in surficial layer (Danovaro and Fraschetti 2002;Kotwicki et al 2005;Giere 2009), rarely exceeding 5-10 cm depth and therefore contamination from the surrounding sediments is excluded. The bottom of the tube remained open.…”
Section: Experimental Design and Sampling Sitementioning
confidence: 99%
“…However, studies on the ecological importance of these three components are still scarce (Koop and Griffiths 1982;Novitsky and Macsween 1989;Sundbaeck et al 1996;Albertelli et al 1999;Jedrzejczak 2002;Fabiano et al 2004;Kotwicki et al 2005;Moreno et al 2005a,b). Moreover, datasets deriving from sampling activities simultaneously targeted at the afore-mentioned benthic components are very rare, especially for the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%